MON-LB108 Measurement Of Carotid Intima,hepatic Steatosis And Inflammatory Markers In Obese Children - Bazan, Maria Cristina (J Endocr Soc, 2020)
Measurement of carotid intima,hepatic steatosis and inflammatory markers in obese children. Elevated levels of inflammatory factors and increased mean intimal carotid thickness (IMT) would increase the risk of atherothrombotic events and contribute to the progression of cardiovascular disease in obese children. Objectives: Evaluate inflammatory factors, metabolic syndrome and non-alcoholic liver steatosis and carotid IMT as an early cardiovascular risk marker. Patients and methods: Descriptive cross-sectional exploratory study. Consider 41 obese children both sexes between 6- 12 years old. Evaluated: anthropometry and determinations of lipid and liver profile, blood glucose, insulin, HOMA, ultrasensitive CRP, fibrinogen. Hepatic ultrasound and measurement of carotid IMT with ESAOTE Mylab 50 Exdicion equipment. . Results: From 41 studied patients, 57% were female. 51% presented MS and 68% elevated triglycerides. CRP> 1 was found in 71% of cases. Hepatic steatosis was observed in 60%, which only 10% had altered transaminases. 12% presented high fibrinogen. Patients with MS had a significant positive difference in the IMTCC (X = 0.41 ± 0.12; p 0.024), HDL (X 37.89 ± 1.72; p 0.004) triglycerides (X 149.42 ± 10.69; p 0.002) in relation to patients without MS. Conclusion: CRP is an inflammatory risk factor associated with elevated BMI and MS. There was a higher prevalence of MS in our study. The increase in the average intimal thickness is significantly related to the presence of MS and RCP>1. The determination of marker molecules of an inflammatory state and measurement of carotid IMT would contribute to the implementation of strategies to prevent cardiovascular, hepatic and metabolic risk since childhood.